Moral And Spiritual Education In Buya Hamka's Educational Thought - Affan Haydar; Siti Mahmudah Noorhayati (Al-Hikmah: International Journal of Islamic Studies, 2026)
The rapid transformation of modern society driven by technological advancement, globalisation, and socio-cultural change has generated significant challenges for Islamic education, particularly in addressing moral decline, spiritual alienation, and the dehumanisation of educational practices. This study aims to analyse the concepts of moral and spiritual education in the thought of Buya Hamka and examine their relevance to contemporary Islamic education. The research employs a qualitative library research approach using philosophical hermeneutics as the primary analytical framework. Primary data were derived from Hamka’s major works, including Tasawuf Modern, Lembaga Budi, Pribadi Hebat, and Tafsir al-Azhar, while secondary data were obtained from scholarly books, journal articles, and related academic studies. Data were analysed through content analysis and contextual interpretation to identify the fundamental principles and educational implications of Hamka’s ideas. The findings reveal that Hamka’s educational philosophy is founded upon an integrative paradigm that harmonises intellectual, moral, and spiritual dimensions. Moral education is centred on character formation through value internalisation, exemplary conduct, and ethical habituation, while spiritual education emphasises the strengthening of faith, worship, self-control, and inner purification through the framework of modern Sufism. The novelty of this study lies in its integrated examination of morality and spirituality as a unified epistemological foundation of Islamic education. The study concludes that Hamka’s thought offers a relevant and transformative educational paradigm capable of addressing contemporary moral and spiritual crises while promoting holistic human development based on religious humanism and Islamic values.